Journey in Religious Pictures: Holy Figures in Renaissance and Baroque Landscapes - Isman, Sibel Almelek (European Scientific Journal, ESJ, 2017)
Artists have portrayed the beauty and glory of nature since Antiquity. Renaissance and Baroque painters depicted religious episodes in impressive landscapes. The aim of this paper is to examine the sceneries which picturise the journey of a biblical figure or a saint. There are many stories in the bible which involve voyage either on the earth or from the earth towards the heaven. Noah built an ark for himself, his family and the animals and they rode safely in the flood. Abraham sent Hagar and their son Ishmael into the wilderness of Beersheba. Lot, his wife and two daughters left the wicked city of Sodom. Jacob dreamed a ladder set up on the earth toward reached the heaven. The Book of Exodus tells the journeys of Moses. He was put in a basket and left in Nile when he was a baby and later in his adult life he passed through the Red Sea with the children of Israel. Gospels describe several journeys. Three wise men made a trip to see the newborn Jesus. An angel appeared to Joseph and warned him to flee into Egypt with the Infant Jesus. Jesus walked on the Sea of Galilee, when his disciples were waiting on the boat. Jesus was led away to be crucified in the pictures called The Road to Calvary. Jesus walked with two of his disciples on the road to the village of Emmaus. The Ascension of Jesus is his departure from earth into the presence of God. Mary’s soul leaves her body in the scenes called Assumption of Mary. Saint Christopher is painted wading through the water with the Infant Christ on his soulders.